Functional Outcome for Arthroscopic Treatment of Septic Arthritis of the Wrist - Chow, Esther M. W.; Lau, Jimmy K. Y.; Liyeung, Lucci L. C.; Chau, W. W.; Mak, Michael C. K.; Tse, W. L.; Ho, P. C. (Journal of Wrist Surgery, 2020)
Background Septic arthritis is a potentially joint-destructing condition if not treated properly. Septic wrist accounts for ∼5% of all septic arthritis. Arthroscopic lavage is a well-documented treatment for septic arthritis of the knee, hip, or shoulder only. Previous studies on septic wrist were limited to case reports or retrospective studies focusing on open treatment, and functional outcome was seldom documented. Our study aims to evaluate the effectiveness of arthroscopic treatment and to investigate the functional outcome.Materials and Methods Patients were retrospectively reviewed over a period of 10 years. Parameters including age, gender, history of prior injury, duration of symptoms, joint aspirates and intraoperative tissue culture, radiological and arthroscopic findings, antibiotics used, number of operations, and hospital stay were reviewed. Functional outcomes were evaluated with QuickDASH (disabilities of the arm, shoulder, and hand) score.Results From 2007 to 2016, 14 patients (15 septic wrists) underwent arthroscopic surgery. One patient had bilateral involvement. The average age was 63.9 years and the average duration of symptoms was 6.08 days. Average follow-up time was 10 months. All except two patients (85.7%) responded to single arthroscopic treatment. Two required subsequent operations for concomitant tenosynovitis. There were no major complications. The most common isolated organism was Staphylococcus aureus. Only one case had severe joint erosion during follow-up. The average QuickDASH score was 19.7. Duration of symptoms 5 days or more before admission was associated with higher QuickDASH score (p = 0.04).Conclusion Early arthroscopic treatment should be considered for all patients admitted for septic arthritis of the wrist if not contraindicated.Level of Evidence This is a Level III, retrospective review.
Keywords: septic wrist; septic arthritis; arthroscopy; infection